Patient’s Safety as Integrated Part of Medical Curricula: Perceptions of Postgraduate Medical Doctors from Two Selected Teaching Institutes Peshawar Pakistan (Medical Forum Monthly, 2024)
Objective: To Perceptions of postgraduate medical doctors Patient’s safety as integrated part of medical curricula in Peshawar Pakistan.Study Design: Qualitative studyPlace and Duration of Study: This study was conducted at the Department of Pediatrics, Khyber Institute of Child Health, Peshawar and Rehman Medical College Peshawar from April 2010 to May 2016.Materials and Methods: This was a qualitative study based on exploratory design where data was gathered through focus group discussion (FGDs) from post graduate medical doctors (Trainee Medical Officers, TMO) from two selected teaching hospitals i.e. Hayatabad Medical Complex (HMC) and Rehman Medical Institute (RMI) Peshawar. Thematic data analysis was done manually for construction of results in terms of narrationsResults: The basic definition of the patient’s safety to them was “health care provision in such that there is no harm to the patients” while incorrect diagnoses and treatment was considered as medical error. Other reported characteristics related medical error are; ignoring patients, lack of skills of procedure and any unethical conducts. One of the senior TMOs explained it in these words “major component of medical error is incorrect diagnose, doctors usually miss diagnose the patients and later realize their mistake”. Based on these definition almost all of the respondents accepted that everybody (doctor) experienced some sort of these incidents or medical errors during the journey of their career, most likely during house job the error took placed. The human factors in this regards included; work burden, fatigue, dealing with complex cases and attitude of the individual doctors and poor hospital management supervision system. Incident reporting system in the hospitals are not implemented yet in the teaching hospital. The participants were of the view that patient’s safety concerns are given due importance in medical curriculums of Pakistan.Conclusion: Patients’ safety was considered as core component of clinical practices. It was emphasized that Patients’ safety module is needed to be formally incorporated in undergraduates and post graduate medical curriculum in Pakistan.